Fancy pumpkins - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The year 2000 was a very good one for pumpkin growers on the Pacific Island of Tonga. Exports rose by 33% to almost US$ 8 million. The principle market is Japan, which also imports pumpkins from Pacific Islands such as Vanuatu and New Caledonia.